Identification of 46 CAG repeats within PPP2R2B as probably the shortest pathogenic allele for SCA12. Issue 4 (April 2015) - Dong, Yi; Wu, Jian-Jun; Wu, Zhi-Ying
Abstract: Background: Spinocerebellar ataxia type 12 (SCA12) is predominantly characterized by action tremor, followed by slowly progressive cerebellar dysfunction. It is a very rare disorder and only identified in certain countries so far. The current appreciation for phenotypic and genotypic features of SCA12 is still limited. Methods: We investigated CAG copies within PPP2R2B in 29 patients with spinocerebellar ataxia who are excluded from the most common SCA subtypes including SCA1, SCA2, SCA3 and SCA6. The medical data of patients carrying abnormal expanded PPP2R2B allele were reviewed and summarized. Results: We found that 3 patients carried 53, 46 and 54 CAG repeats respectively, while the other 26 cases harbored CAG repeats less than 30. The probably shortest pathogenic allele of 46 repeats was detected in one kindred typically experiencing action tremor. Additionally, compared to the prominent cerebellar ataxia, nystagmus and dysphagia seem to be rare in our SCA12 patients. Conclusions: SCA12 might not be as rare in Chinese as previously assumed. The identification of the shortest pathogenic allele helps to define the minimal limit implicated in the disease onset. Moreover, the disease manifestations distinct from other SCA subtypes could help clinicians to provide timely genetic counseling. Highlights: We report three Chinese pedigrees with SCA12. 46 CAG repeats is probably the shortest pathogenic allele for SCA12. Action tremor could be absent in disease course of SCA12. Nystagmus and dysphagia appear to be rare in our SCA12 patients.